Pneumatization pattern of the temporal bone with volumetric assessment and its impact on the frequency of cerebrospinal fluid leak in patients undergoing vestibular schwannoma surgery via the retrosigmoid approach - Zaczkowski, Karol; Wójcik, Rafał; Tybor, Krzysztof; Jaskólski, Dariusz Jan; Wiśniewski, Karol (Frontiers in Neurology, 2024)
IntroductionVestibular schwannomas are benign tumors that account for 8% of all intracranial tumors. Due to their location in the cerebellopontine angle and internal auditory canal, access to these lesions requires disruption of the temporal bone. The pneumatization of this bone varies between individuals, and literature reports suggest that it may influence the frequency of cerebrospinal fluid leaks. In our study, we assessed whether the pneumatization of the temporal bone differs in individuals with or without cerebrospinal fluid leak.MethodsWe conducted a retrospective analysis that initially included 143 individuals, of whom 103 were ultimately qualified for the study. We analyzed the clinical data of the patients and the radiological characteristics of the pneumatization of the temporal bone using volumetric methods, additionally relying on classifications of temporal bone pneumatization.ResultsPneumatization of the temporal bone in patients operated on for vestibular schwannoma with cerebrospinal fluid leakage was significantly higher compared to the group without leakage (Right: 11.15 [IQR 8.93–12.83] vs. 13.25 [IQR 10.15–15.53]; p = 0.040; Left: 10.95 [IQR 9.5–12.26] vs. 14.4 [IQR 13.03–15.7]; p = 0.012). Additionally, a higher degree of pneumatization of the petrous apex was significantly more frequent in the group with cerebrospinal fluid leak in both left (p < 0.001) and right (p < 0.001) side.DiscussionThe analyzed data suggest that greater pneumatization of the temporal bone and a higher degree of petrous apex pneumatization in the classification of temporal bone pneumatization may be associated with an increased risk of cerebrospinal fluid leak. To draw causal inferences, prospective studies in this area are necessary.